If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -58 + 9x = 3x + 20 Reorder the terms: -58 + 9x = 20 + 3x Solving -58 + 9x = 20 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. -58 + 9x + -3x = 20 + 3x + -3x Combine like terms: 9x + -3x = 6x -58 + 6x = 20 + 3x + -3x Combine like terms: 3x + -3x = 0 -58 + 6x = 20 + 0 -58 + 6x = 20 Add '58' to each side of the equation. -58 + 58 + 6x = 20 + 58 Combine like terms: -58 + 58 = 0 0 + 6x = 20 + 58 6x = 20 + 58 Combine like terms: 20 + 58 = 78 6x = 78 Divide each side by '6'. x = 13 Simplifying x = 13
| 4x^2-9y^2+18y-45=0 | | 2x-75=-12x+107 | | 0=-2*sin(2x) | | 19/2-[9/2{5/2-9/2-4}] | | (x+0.05)y=1.05y*x | | -41-x=19-5 | | X-7=x+19 | | 3w+3x=99 | | 3k^2-12k+12=75 | | -20+4x=43+x | | 2w+1x=49 | | 3k(k+1)=0 | | 9x-2=6x+13 | | 2x^2-5x-3=-3 | | 2x-5y+5xy=14 | | 2xy-5y+5xy=14 | | 36x-54+49=0 | | 2x^4/6x^2 | | y=32x+2 | | y=22x+1 | | 22=ax+1 | | 16-3x=36-8x | | 2x+7=19-2x | | 5ab+3ba= | | x/=6 | | so/ve | | y=x^3+9x-1 | | 3x+11=-17-4x | | 28p=70 | | 0.16x=1 | | f(x)=x^3-x^2+8x | | 80d=60 |